Why some leaders thrive and others derail - Kets de Vries, Manfred F. R. (Henry Stewart Talks, 2022)
Hubris, Coaching, Leadership team, Team culture, Narcissistic leaders, Workplace toxicity, Communication, Self-doubt, Constructive narcissism, Destructive narcissism